Warehouse Relayout Design with Weighted Distance Method to Minimize Time Travel - Adi Firmansyah; Lukmandono Lukmandono (Petra International Journal of Business Studies, 2020)
Global competition between companies is becoming increasingly stringent, resulting in companies having to understand their customers better. Customers no longer only need quality products, but also need excellent and timely service. To meet the desires of these consumers, the company must create an effective and efficient work system. PT IJS is a warehouse engaged in logistics services in the Perak area of Surabaya. One of the services provided by PT IJS is bonded warehouse logistic services. A bounded warehouse owned is currently not able to provide maximum service because there are still many late deliveries that do not send goods to the port, and there is a closing time that is detrimental to the customer. The length of the delivery process is due to several factors, one of which is a less effective warehouse layout. Travel time is the time required for a vehicle to carry out activities loading goods PT. IJS from arrival to exit the warehouse. The method weighted distance is a mathematical model used to evaluate the layout based on proximity factors. The design of the layout design by using the technique weighted distance produces an alternative layout that shows calculation travel time a shorter